Governance and leadership in education policy making and school development in a divided society. (15th March 2021) - Gallagher, Tony
ABSTRACT: The Good Friday Agreement (1997) brought political violence in Northern Ireland to an end and provided the basis for shared government. A consociational political structure was adopted which institutionalised community differences while encouraging coalition government. The goal was that a requirement for consensus decisions would encourage cooperation between political leaders and promote effective decision-making. This paper examines the period of devolved government in Northern Ireland from 1998 to 2017 through the lens of education policy to explore leadership on these issues. The paper will examine three policy issues: a review of the effects of academic selection in post primary education; a proposal to rationalise the administrative arrangements in education; and an initiative to promote collaborative networks between separate denominational schools through 'shared education'. The paper will conclude that, far from providing a superordinate goal around which the different political parties could coalesce, there was a lack of systemic leadership on educational debates. Inability in most cases to establish consensus resulted in policy paralysis. The one area where this did not occur was the adoption of 'shared education' which may have been because this initiative was a bottom-up process based on the empowerment of teachers.